Analysis of Leader Member Exchange - Adi Santoso; Fitri Suratin (Faculty of Economic and Business, 2016)
This research aims to find out how the relationship of superiors and subordinates works or we call it, LEADER MEMBER EXCHANGE (LMX) in another term. The object of this research is an Integrated Nursing Home for Impaired Speech and Hearing (INISPH), ''Meohai” Kendari, with 5 superiors and subordinates of this institution as the research informants. The method used in this research is descriptive qualitative analysis. The research found that the relationship of superiors and subordinates or Leader Member Exchange (LMX), has been well-intertwined, based on the affection, loyalty, enormous contribution, and respect one another toward the profession done in creating a close relationship to achieve the goal.DOI: 10.15408/etk.v15i2.3244